PENGARUH KESADARAN MEMBAYAR PAJAK, PENGETAHUAN DAN PEMAHAMAN PERATURAN PERPAJAKAN, SERTA PERSEPSI ATAS EFEKTIFITAS SISTEM PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK DALAM MELAPORKAN SPT DI SEMARANG (Students' Journal of Accounting and Banking, 2014)
The main objective of this study was to analyze the extent to which if external factors on the level of tax compliance in Semarang. External factors in this study were the awareness of tax paying, knowledge and understanding of the regulations, perception of tax system effectiveness. This study was based on a sample of 54 personal taxpayers, representing about 73 percent of the total population. Respondents consists of lecturers of local universities in Semarang. Data were analyzed by using multiple regression method with the use of t-test. The hypothesis test showed that the awareness of tax paying, knowledge and understanding of tax regulations had atau significant positive effect of tax payer compliance. While the perception of tax system effectiveness had no effect on tax payer compliance.Keywords: tax payer compliance, awareness of tax paying, knowledge and understanding of tax regulations, perception of tax system effectiveness